Streaming Potential Coefficient Measurements in Porous Rocks Saturated by Divalent Electrolytes - Duy Thanh, Luong; Manh Hung, Nguyen; Minh Hue, Dang Thi; Chung Thuy, Tran Thi (VNU Journal of Science: Mathematics - Physics; Vol 36 No 4, 2020)
Streaming potential in a water-rock system is generated by the relative motion between water and solid surfaces and is directly related to the existence of an electric double layer between water and solid grain surfaces of porous media. The streaming potential measurements have great potential in geophysical applications. Most porous rocks are filled by ground water containing various types of electrolytes. Therefore, it is important to understand the variation of the streaming potential with types of electrolytes for specific rocks. In this work, we have carried out streaming potential measurements for three consolidated rocks saturated by three divalent electrolytes at different electrolyte concentrations. The experimental result shows that the streaming potential coefficient in magnitude of all samples decreases with increasing electrolyte concentration. Additionally, an empirical relation between the streaming potential coefficient and the electrolyte concentration is obtained and it has a similar form to those available in literature for monovalent electrolytes.